Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Travel Umrah Di Pt. Amanah Fadlilah Insan Lumajang - Junaedi Junaedi; Umi Suswati Risnaeni; Nurhafid Ishari (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2018)
Customer satisfaction will be formed if it can meet customer base expectations. Many factors influence customer satisfaction, including service quality and price. The purpose of this study is (1) to analyze the effect of service quality on customer satisfaction, (2) to analyze the effect of prices on customer satisfaction (3) to analyze the effect of service quality and price on customer satisfaction at PT. Amanah Fadlilah Lumajang personnel. The population in this study were Umrah members from 2015 to 2017 at PT. Amanah Fadlilah Ihsan Lumajang. Samples were determined by the technique of sample areas with 147 respondents. Data collection methods used are questionnaires and documentation. Data analysis techniques used in this study are instrument tests (validity and reliability testing), simple linear regression analysis, hypothesis testing, and determination coefficients using the SPSS program. The results of this study obtained a simple linear regression equation Y = 2.322+ 0.173 X1 + 0.742 X2. (1) There is an influence between the quality of service partially with a value of t = 2.831. (2) There is a price effect on customer satisfaction partially with a value of t = 10,649. (3) Overall service quality and prices affect customer satisfaction by 55.8%. Based on the results of the above research it can be concluded that there is a significant influence on service quality and price on customer satisfaction at PT. Amanah Fadlilah Lumajang personnel.